HUBUNGAN PENGETAHUAN, SIKAP, DAN PERAN KELUARGA, SERTA LINGKUNGAN SOSIAL TERHADAP UPAYA PENCEGAHAN PENGGUNAAN NARKOBA PADA SISWA/I DI SMP N 1 BANGKINANG - Rusdi, Muhammad; Puteri, Ade Dita (Universitas Pahlawan Tuanku Tambusai, 2023)
Drug abuse is mostly common in adolescents, because adolescence is a period of transition and adolescents begin to look for identity. Drugs are chemical substances that are inserted into the human body either swallowed through the mouth, inhaled through the nose, or injected through the blood vessels. Continuous use will result in physical and or psychological dependence. The most common risk is damage to the nervous system and important organs. This study aims to determine the relationship of knowledge, attitudes, family roles and social environment to efforts to prevent drug use at SMP N 1 Bangkinang in 2022. This type of research is a quantitative research, analytic survey with a cross sectional approach. The population in this study were students of class VIII SMPN 1 Bangkinang totaling 85 people. This study uses a total sampling technique with a total sample of 85 people. The variables in this study were knowledge, attitudes, family roles and social environment. Data analysis used was univariate and bivariate analysis using chi-square test. The results of the study using statistical tests showed that there was a significant relationship between family role factors and efforts to prevent drug use in students of SMP N 1 Bangkinang, namely with (p value = 0.000), students' social environment factors (p value = 0.005), student attitude factors (p value = 0.008), student knowledge factor (p value = 0.028). Efforts to prevent drug use can be prevented from the role of the family towards students that occur in the home. A good home education is a good action to determine the future of a student. And a good social environment is something that can be done to prevent drug use.